Cervical spine immobilisation is only required in drowning patients at high risk of axial loading of the spine. (25th July 2022) - Thom, Ogilvie; Roberts, Kym; Leggat, Peter A; Devine, Susan; Peden, Amy E; Franklin, Richard
Abstract: Objectives: Wave forced impacts are known to result in cervical spine injuries (CSI) and approximately 20% of drownings in Australia occur at the beach. The most common mechanism of injury in studies examining the frequency of CSI in drowning patients is shallow water diving. The aim of the present study was to determine what proportion of CSIs occurring in bodies of water experienced a concomitant drowning injury in a location where wave forced impacts are likely to be an additional risk factor. Methods: Electronic medical records at the Sunshine Coast Hospital and Health Service EDs, Queensland Ambulance Service case records and Surf Life Saving Queensland data between 1 January 2015 and 21 April 2021 were manually linked. Outcomes recorded included victim demographics, scene information, hospital course and patient disposition. Results: Ninety‐one of 574 (15.9%) CSIs occurred in a body of water with risk of drowning. However, only 4 (4.3%) had a simultaneous drowning injury, representing 0.8% (4/483) of drowning presentations. Ten (10.9%) patients reported loss of consciousness, including the four with drowning. The principal mechanism of CSI was a wave forced impact (71/91, 78%). Most injuries occurred at the beach (79/91, 86.8%). Delayed presentation was common (28/91, 31%). A history of axial loading was 100% sensitive when indicating imaging. Conclusions: The combination of CSI and drowning is uncommon. Cervical spine precautions are only required in drowning patients with signs or a history, or at high risk of, axial loading of the spine. This paper supports the move away from routine cervical spine precautions even in a high‐risk population. Abstract : Wave forced impacts result in large numbers of cervical spine injuries (CSIs). Fortunately, the combination of CSI and drowning is uncommon. Cervical spine immobilisation is only required in drowning patients at high risk of axial loading of the spine.